Inhibition of Notch Signaling Stimulates Osteoclastogenesis From the Common Trilineage Progenitor Under Inflammatory Conditions - Filipović, Maša; Flegar, Darja; Šućur, Alan; Šisl, Dino; Kavazović, Inga; Antica, Mariastefania; Kelava, Tomislav; Kovačić, Nataša; Grčević, Danka (Frontiers in Immunology, 2022)
Osteoclasts, dendritic cells (DCs) and macrophages can be derived from a common trilineage myeloid progenitor of hematopoietic origin. Progenitor commitment is susceptible to regulation through Notch signaling. We aimed to determine the effects of Notch modulation on trilineage progenitor commitment and functional properties of differentiated cells under inflammatory conditions. We used the conditional inducible CX3CR1CreERT2 mouse strain to achieve overexpression of the Notch 1 intracellular domain (NICD1) or to inhibit Notch signaling via deletion of the transcription factor RBP-J in a bone marrow population, which was used as a source of the trilineage progenitor (CD45+Ly6G−CD3−B220−NK1.1−CD11b–/loCD115+). Cre-recombinase, under the control of the CX3CR1 promoter, expressed in the monocyte/macrophage lineage, was induced in vitro by 4-hydroxytamoxifen. Differentiation of osteoclasts was induced by M-CSF/RANKL; macrophages by M-CSF; DCs by IL-4/GM-CSF, and inflammation by LPS. Functionally, DCs were tested for the ability to process and present antigen, macrophages to phagocytose E. coli particles, and osteoclasts to resorb bone and express tartrate-resistant acid phosphatase (TRAP). We found that Notch 1 signal activation suppressed osteoclast formation, whereas disruption of the Notch canonical pathway enhanced osteoclastogenesis, resulting in a higher number and size of osteoclasts. RANK protein and Ctsk gene expression were upregulated in osteoclastogenic cultures from RBP-J+ mice, with the opposing results in NICD1+ mice. Notch modulation did not affect the number of in vitro differentiated macrophages and DCs. However, RBP-J deletion stimulated Il12b and Cd86 expression in macrophages and DCs, respectively. Functional assays under inflammatory conditions confirmed that Notch silencing amplifies TRAP expression by osteoclasts, whereas the enhanced phagocytosis by macrophages was observed in both NICD1+ and RBP-J+ strains. Finally, antigen presentation by LPS-stimulated DCs was significantly downregulated with NICD1 overexpression. Our experimental setting allowed us to define a cell-autonomous response to Notch signaling at the trilineage progenitor stage. Although Notch signaling modulation affected the activity of all three lineages, the major effect was observed in osteoclasts, resulting in enhanced differentiation and function with inhibition of canonical Notch signaling. Our results indicate that Notch signaling participates as the negative regulator of osteoclast activity during inflammation, which may be relevant in immune and bone diseases.